Coproparasitological diagnosis of fascioliasis in sheep and goats from Boavita, Boyacá (Colombia) - Ortiz-Pineda, Melissa C. (2022)
The aim of this study was to establish the prevalence of Fasciola hepatica through coprological analysis and to identify risk factors associated with the presentation of the parasite in sheep and goats in the municipality of Boavita, Boyacá. The study was observational, descriptive, cross-sectional with simple random sampling. Faecal samples were taken from 297 sheep and 337 goats to identify parasite eggs. The general prevalence was 8.0% (51/634), being 9.1% for sheep and 7.1% for goats. The prevalence in sheep was higher in males (14.8%) than in females (8.5%), likewise, sheep less than one year old (9.3%) and Criolla (11.1%) presented the highest prevalence. In goats, the prevalence was higher in females (7.3%) than in males (5.6%), and those less than one year old (10.5%) and the Alpine breed (8%) presented the greater prevalence. No significant statistical association was found between females and males. The Creole breed was established as a risk factor for sheep.